Poco-A-Poco: An OR Nurse’s Experience of a Lifetime - McLennan‐Robbins, Kim (Operating Room Nurses Association of Canada Journal, 1999)
Poco-a-Poco, which in Spanish means little by little, is a registered charity founded by Jill Sampson, a veterinarian from Qualicum Beach, British Columbia. The society was formed in 1995 after she realized the need for surgical services in and around Antigua, Guatemala.